Ansiedad ante las ciencias y pruebas de evaluación científicas: efectos del nivel académico y género - Benlloch Pla, Marc; Solaz Portolés, Joan Josep; Sanjosé López, Vicent (Revista Científica, 2019)
In this paper is carried out a first approximation to anxiety surrounding situations related to science. One hundred and seventy-five spanish secondary education students at different educational levels have been administered two validated tests and a scientific competencies assessment test. One test measures the anxiety caused by scientific contexts, and the other test assesses the science assessment test anxiety. The analysis of the results obtained by means of Anova tests allow us to conclude that: a) the anxiety in scientific situations is greater than the non-scientific situations, and this anxiety gets smaller as the school grade level increases. ; b) the science assessment test anxiety is statistically significantly higher for women than for men; and c) there is no evidence of a significant correlation between the science assessment test anxiety and science test scores.